Multiple sclerosis and dizziness in the elderly - Magdalena Węgrzyn; Kinga Olesinkiewicz; Karolina Kubiak; Martyna Lamtych; Aneta Karło; Marlena Kontowicz; Aleksandra Wijata; Olga Rymarska; Pamela Świerczek; Klaudia Kwiatkowska; Agata Sochań (Kazimierz Wielki University, 2019)
Background:The essence of sclerosis disseminated, characteristics of the symptoms of this disease and familiarization with the main difficulties that sick people face. Material and methods:The methods used to treat balance disorders and dizziness are pharmacotherapy, vestibular rehabilitation, lifestyle changes and surgical treatment. Results: The results are not very optimistic, treatment is not too easy symptoms are manifested in motor dysfunction leading to even disability Conclusions:Multiple sclerosis is a disease affecting the nerve center of unknown etiology which makes treating difficult. The onset of the disease is often dizziness or headache.